An unusual gait following the discovery of a new disease. Issue 2 (8th March 2011) - Keogh, M J; Khan, A; Gorman, G; McNeill, A; Horvath, R; Burn, J; Chinnery, P F
Abstract : A 39-year-old woman presented to the neurology clinic with an abnormal gait. Subsequent investigations confirmed a rare neurodegenerative disease. This case highlights the key clinical features and diagnostic approach to neuroferritinopathy, and describes the discovery of the disease in a family from Cumbria in the north west of England.